Facile gamma radiolytic methodology for TiO2-rGO synthesis: effect on photo-catalytic H-2 evolution - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dhara, S.; Dash, Sitaram; Tyagi, A. K. (International Journal of Hydrogen Energy, 2015)
TiO2 (P25) decorated reduced graphene oxide (rGO) is synthesized by gamma-radiolytic technique using water-ethanol solvent medium. Visible light absorpdon was confirmed by UV-Visible spectroscopy. Photoluminescence (PL) study revealed a decline in electron-hole recombination rate signalled by a sharp fall in luminescence of TiO2. Under such scenario, electron transfer from TiO2 conduction band to the conjugated sheet becomes a preferred pathway in the presence of rGO, which is further confirmed by photocurrent measurement. TiO2 -rGO composite with 1 wt. % rGO was found to be the best composition in terms of visible light absorption, while retaining TiO2 crystallinity. Transmission electron microscopy and Raman spectroscopic studies confirmed the coating of rGO sheet with TiO2 nanoparticles. TiO2 -rGO was found to show about 150 times higher photocatalytic H-2 generation under 250 W UV-Visible light irradiation than pristine TiO2. In addition to this, TiO2 -rGO composite shows hydrogen production yield of 35 mu mol/h.g under visible light (lambda = 400 nm) irradiation. Thus gamma-radiolysis can be considered to be a viable technique, which helps in synthesizing photocatalytically active nanocomposite with high H-2 evolution rate. In the light of these interesting aspects, a detail investigation is carried out to study the effect of rGO concentration and illumination time on photocatalytic yield. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: gamma-radiolysis; H-2 production; Photocatalysis; Reduced graphene oxide; TiO2

TiO2 modification by gold (Au) for photocatalytic hydrogen (H-2) production - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dash, Sitaram; Tyagi, A. K. (Renewable & Sustainable Energy Reviews, 2016)
TiO2 is indeed one of the widely used semiconductors employed for photocatalytic hydrogen production. Most of its photocatalytic activity-is achieved in its crystalline form. However, its photocatalytic activity is limited to ultraviolet region. For making TiO2 visible light active; Au deposition is strongly recommended due to its surface plasmon feature. Au deposition enhances the photocatalytic activity of both crystalline and nanocrystalline TiO2. Efficiency of photocatalytic activity is controlled by shape and size of Au nanoparticle subsequently the synthetic methodology plays an important role. Herein, we furnish a brief description of TiO2-Au nanocomposite synthesis by different methods viz. sol-gel, photodeposition, deposition-precipitation simple reducing method and dispersion method. A discussion on physical properties of the resultant material is also provided. Three different types of mechanism has been described depending on the type of irradiation and form of TiO2 (crystalline and nanocrytalline). A comparative hydrogen production yield is also tabulated to get an idea about the best synthesis methodology and form of TiO2 for efficient photocatalysis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gold nanoparticle; Hydrogen generation; Nanocomposite; Photocatalysis; TiO2